Polarization Sensitive Optical Coherence Tomography for Materials Characterization - Kunakorn Palawong (Science Faculty of Chiang Mai University, 2019)
Polarization sensitive optical coherence tomography (PS-OCT) is an extension of optical coherence tomography (OCT), which is a technique of non-contact and non-destructive 3D imaging. PS-OCT can provide cross-sectional image of not only the inner structure of a sample but also its birefringence properties, such as phase retardation and crystal axis orientation. In this paper, the implementation of our custom-designed PS-OCT system is descripted. The developed PS-OCT system has been designed for characterization and investigation of the birefringence properties of fibrous materials. Examples of the application of the developed PS-OCT for characterizing the birefringence of a cover slide glass, a multi-layered plastic tape, and a thin film of fibrous materials fabricated by electrospinning technique are presented. The experimental results verified that the implemented PS-OCT system can differentiate between isotropic and anisotropic media.